Effects of compound-326, a selective delta-5 desaturase inhibitor, in ApoE knockout mice with two different protocols for atherosclerosis development - Hiroki Nagase; Shuichi Takagahara; Yoshinori Satomi; Ayumi Ando; Kazuki Kubo; Shota Ikeda (Frontiers Media S.A., 2021)
Purpose: We previously confirmed its anti-atherosclerotic effects by pre-treatment with compound-326, a selective delta-5 desaturase (D5D) inhibitor, in Western diet-fed ApoE knockout mice. In the present study, we evaluated effects of compound-326 in ApoE knockout mice with two different protocols for atherosclerosis development. Methods: In a post-treatment protocol, where the compound treatment started after 10 weeks pre-feeding of Western diet, compound-326 (1 and 3 mg/kg/day, p.o. for 12 weeks) significantly reduced the atherosclerotic lesion area in the aorta (24% reduction at 3 mg/kg/day). In another protocol using Paigen diet (containing 12.5% cholesterol and 5% sodium cholate), compound-326 (3 and 10 mg/kg/day, p.o. for 7 weeks) also significantly reduced the lesion area (36% reduction at 3 mg/kg/day). Results: In both protocols, Compound-326 significantly reduced the hepatic ratio of arachidonic acid to dihomo-γ-linolenic acid, blood inflammatory eicosanoid production and plasma soluble intercellular adhesion molecule 1 (sICAM-1) levels, similarly to the previous pre-treatment study. Conclusions: Compound-326 exerted anti-atherosclerotic effects in ApoE knockout mice with the two different protocols for atherosclerosis development further supporting D5D inhibition as a promising strategy in treating atherosclerosis.